Community Perception on Land Dispossession and Compensation Practices: Evidence from Gondar City, Northwest Ethiopia - Alebachew Destaw Belay; Mitikie Nigussie Melesse (International Journal of Land, 2026)
Land expropriation for urban expansion in the Gondar area significantly reduced farming households from 95%–74%, displacing 29% of affected farmers. While some acknowledged the public benefits, most respondents criticized the process for a lack of transparency, limited community involvement, and inadequate rehabilitation support. Farmers reported receiving compensation that was low, unfairly calculated, and subject to prolonged delays. Key systemic issues included a lack of awareness among affected communities, inconsistent knowledge among officials, and an absence of accountability and transparent practices. The local government’s role was seen as ending with compensation, failing to ensure sustainable livelihoods. To address these, the study recommends coordinated awareness training for both communities and executing agencies. The process of acquiring land should be open and involve community participation. Most importantly, local governments must prioritize rehabilitating displaced individuals by organizing skill training and developing business plans, ensuring equitable outcomes beyond mere financial payment. Furthermore, the findings underscore the need for an integrated policy framework that links land expropriation with long-term urban and rural development planning. Strengthening institutional capacity, establishing clear monitoring and evaluation mechanisms, and enforcing legal safeguards can enhance fairness and public trust in expropriation practices. Incorporating livelihood restoration programs into compensation schemes would reduce socio-economic vulnerability and improve resilience among displaced households. Overall, adopting participatory, transparent, and accountable approaches is essential for balancing urban growth objectives with social justice and sustainable development.
Keywords: Compensation; dispossession; land; perception; urbanization